Strategi Pemasaran Beras Semi Organik di Gapoktan Saluyu Kecamatan Cilamaya Wetan Kabupaten Karawang - Odeta Riaviola; Muharam Muharam; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Semi-organic agriculture is one of the ways to achieve environmentally friendly and sustainable agricultural development. Semi-organic rice is an organic agricultural product whose cultivation is still using low doses of chemical fertilizers without chemical pesticides. The purpose of the study was to determine the factors of strengths, weaknesses, opportunities, threats, alternative strategies and strategic priorities in marketing semi-organic rice in Gapoktan Saluyu. The research method used a descriptive method with a mixed method approach. This study used secondary data and primary data. Primary data collection with interview techniques using questionnaires. The research respondents were seven semi-organic rice farmers, the head of Gapoktan saluyu, an agricultural extension worker at Cilamaya Wetan, a middleman, two consumers, the Karawang regency agriculture office, modern retailers, and academics. Secondary data were obtained from the Central Statistics Agency, the Karawang Regency Agriculture Office and the Cilamaya Village Office. The sample of farmers and stakeholders was determined by purposive method with considerations according to their field of expertise. The analysis technique used is the IFE matrix and the EFE matrix, the SWOT matrix and the QSPM matrix. The results of the study show that the main factors are guaranteed product safety, lack of distribution channels in West Java and outside Java, increasing market prospects and global demand, and increasing organic business competition. The results of the SWOT matrix analysis produce five strategies. Based on the analysis of the QSPM matrix, expanding the market network by collaborating with traders or retailers is a strategic priority with the highest Sum Total Attractiveness Score (STAS) of 7.06.